Alkaline phosphomonoesterase-harboring bacteria facilitate phosphorus availability during winter composting with different animal manures. (20th November 2022) - Cheng, Yarui; Wan, Wenjie
Abstract: Scientific understanding of ecological role of alkaline phosphomonoesterase ( phoD )-harboring bacteria in phosphorus availability is lacking during composting. To explore ecological functions of phoD -harboring bacteria and differences in compost properties among four animal (i.e., pig, chicken, cow, and sheep) manure groups, we conducted small-scale composting and applied Illumina MiSeq sequencing and multiple statistical analyses. Results displayed notably shifts in compost abiotic and biotic properties, and phoD -harboring bacteria in the pig manure group showed larger compositional differences, weaker community replacement, more complex coexistence patterns, and stronger environmental constraints than other manure groups. The temperature-affected phoD -harboring bacterial community directly and indirectly shapes compost phosphorus availability, and available phosphorus in the final compost was notably higher in pig manure (1.04 g kg −1 ) group than other groups (0.61–0.78 g kg −1 ). Our findings highlight important ecological roles of phoD -harboring bacteria in phosphorus availability during winter composting, and disentangle that pig manure is superior to other manures for composting. These findings might guide small-scale manure composting, and the final compost can serve as biological phosphorus fertilizer. Graphical abstract: Image 1 Highlights: Available P was significantly higher in pig manure group than other manure groups. Compost enzyme activities were mainly adjusted by temperature and available P. Manure type and temperature affected phoD -harboring bacterial community composition. Weaker species replacement and stronger environmental constraint were in pig manure. PhoD -harboring bacteria directly and indirectly shaped phosphorus availability.